(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Questionnaire is administered on Company Secretaries, Chartered Accountants of different assembling and Service Sector companies of India. Descriptive just as inferential measurements were used for examining information. Information investigation suggested e-filling system need to be strengthened on different parameters like Connectivity with server, Forms position, Ease in imparting data to outsiders, and information Accuracy in India. Ramifications of the examination, impediments and future research directions have additionally been discussed right now.